The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/ejic.201500279
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Synthesis of Siloxane‐Substituted Oligoarsanes and Structural Investigation of Alkaline Earth Metal Derivatives

Abstract: The reaction between [Li(dme)AsH2] and (ClSiiPr2)2O gives a mixture of two products: the primary diarsanyldisiloxan (H2AsSiiPr2)2O (5) and the cyclic diarsanylsiloxane (HAsSiiPr2)2O (6). Through metallation of the mixture, the deprotonated species of both compounds could be obtained and isolated. Further reactions between the two metallated cyclic diarsanylsiloxanes (compounds 9 and 10) and (ClSiiPr2)2O both lead to the bicyclic compound As2[(iPr2Si)2O]2 (11). Subsequent oxidative coupling of 9 or 10 with C2H4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The central structural motif in 3 is the bridging As 3 three-membered ring, which coordinates in η 1 ,η 2 fashion to two Ga atoms. Even though complexes containing cyclic P 3 and As 3 are known, the structural motif as observed in 3 has not been reported previously. Alternatively, the structure of 3 can be described as a LGaAs 3 butterfly-shaped structure, which is η 1 -coordinated by an additional L­(Cp*)Ga fragment.…”
mentioning
confidence: 86%
“…The central structural motif in 3 is the bridging As 3 three-membered ring, which coordinates in η 1 ,η 2 fashion to two Ga atoms. Even though complexes containing cyclic P 3 and As 3 are known, the structural motif as observed in 3 has not been reported previously. Alternatively, the structure of 3 can be described as a LGaAs 3 butterfly-shaped structure, which is η 1 -coordinated by an additional L­(Cp*)Ga fragment.…”
mentioning
confidence: 86%
“…For example, Westerhausen showed that the calcium bis-amide Ca­[N­(SiMe 3 ) 2 ] 2 was able to deprotonate the silylated primary arsine H 2 As–Si i Pr 3 ( 1215 ) generating a new calcium bis­(silyl)­arsenide [Ca­(THF) 4 {AsH­(Si i Pr 3 )} 2 ] ( 1216 , eq 103 ). Related silylarsenides [As­(H)­SiR 3 ] − of strontium, barium, magnesium, zinc and lithium were also reported. …”
Section: Molecular Hydrides Of Group 15 Metals (Arsenic Antimony and ...mentioning
confidence: 99%
“…Therefore, much smaller Si‐O‐Si angles can be imposed in strained cyclic siloxane systems. As suggested by the angle–basicity correlation, their basicity will be substantially higher in comparison to the basicity of siloxane units incorporated into chains and consequently they have different material properties . Hence, the coordination chemistry of cyclic siloxanes has been the focus of much recent research …”
Section: Introductionmentioning
confidence: 99%